Korelasi antara dimensi vertikal oklusi dengan panjang jari kelingking pada sub-ras Deutro Melayu - Cytha Nilam Chairani; Eni Rahmi (Majalah Kedokteran Gigi Indonesia, 2016)
Correlation between VDO with length of little finger in Malay Deutro sub race. The correct determination of vertical dimension of occlusion (VDO) is an important step to to concern for dentist in clinical procedures of dental treatment. VDO is defined as the distance between two selected anatomic points, one point on maxilla and the other on mandibule in centric occlusion. There are various measurements of VDO methods suggested. Recently, many researchers have been studied antropometric method to determine the VDO. One of the antropometric methods is the length of little finger measurement. VDO and length of little finger are influenced by human race and each race has different specific characteristic. This study choose Malay Deutro sub race as one of sub-races in Indonesia. The purpose of this study is to determine the correlation between measurement of DVO and length of little finger of Malay Deutro sub race in Padang. This study use observational analysis with cross sectional approach. The samples consist of 56 males and 56 females, 112 respondents in total. The respondents are Malay Deutro sub race that domicile in Padang and are eligible. The data were analyzed by Pearson correlation test. VDO and length of little finger of Mal ay Deutro sub race was significantly correlated (r value= 0,768) and the result of VDO was almost equal with length of little fi nger (p value= 0,000) that means statistically significant. The Antropometric parameter measurement of the length of little finger can be used in determination of VDO. ABSTRAKPenentuan dimensi vertikal oklusi (DVO) yang tepat merupakan salah satu faktor penting yang perlu diperhatikan dokter gigi dalam prosedur klinis perawatan gigi. DVO adalah jarak antara dua titik anatomi yang dipilih, yaitu satu titik pada maksila dan satu titik pada mandibula ketika posisi oklusi sentrik. Beberapa metode dianjurkan dalam pengukuran DVO. Salah satu metode penentuan DVO yang dikembangkan oleh para ahli yaitu metode antropometri. Metode ini dilakukan dengan cara pengukuran panjang jari kelingking. DVO dan panjang jari kelingking berbeda pada setiap ras manusia karena masing-masing ras memiliki ciri-ciri spesifik yang berbeda antara satu dengan yang lain. Sub ras Deutro Melayu merupakan salah satu sub ras di Indonesia. Penelitian ini bertujuan untuk mengetahui korelasi antara hasil pengukuran DVO dan panjang jari kelingking pada sub ras Deutro Melayu di Kota Padang. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Sampel sebanyak 112 warga Kota Padang yang merupakan sub ras Deutro Melayu dan memenuhi kriteria, terdiri dari 56 orang laki-laki dan 56 orang perempuan. Data diuji secara statistik dengan analisis Pearson correlation. Terdapat korelasi yang bermakna antara hasil pengukuran DVO dengan panjang jari kelingking dengan nilai r=0,768 dan hasil kedua pengukuran ini menunjukkan nilai yang hampir sama dengan nilai p=0,000, sehingga signifikan secara statistik (p<0,05). Pengukuran antropometri panjang jari kelingking merupakan metode yang dapat digunakan untuk menentukan DVO.